HOPCTP: A Robust Channel Categorization Data Preservation Scheme for Industrial Healthcare Internet of Things - Adil, Muhammad; Attique, Muhammad; Jadoon, Muhammad Mohsin; Ali, Jehad; Farouk, Ahmed; Song, Houbing (IEEE Transactions on Industrial Informatics, 2022)
In this article, we present a robust channel categorization scheme to fix data privacy and preservation problems in an Industrial Healthcare Internet of Things (IHC-IoT) network. The proposed model categorizes the transmission bandwidth into four independent channels for each device by defining triggering rules with respect to time for reception and transmission of data. Besides, our developed prototype, which is known as high optimal path channel triggering protocol (HOPCTP) ensures data privacy and preservation utilizing minimal network resources in an IHC-IoT network. Furthermore, the HOPCTP prototype enables client-side devices to transmit and receive data with four different independent communication channels following the triggering mechanism to avoid adversary device anticipation in the network. The categorized channels are triggered with a defined time period to change their transmission and reception functionality, which triggers the transmitted data between different channels. Same data transmission via four different channels ensures the confidentiality and integrity of data because if an attacker captures one channel of data, he will not be able to understand the full message. The convalescent communication infrastructure is developed among patient wearable devices followed by cluster heads, micro base station, and macro base station to ensure data privacy and preservation with better communication metrics. In addition, the objective of the HOPCTP prototype is to resolve the data privacy issues in delay-sensitive applications, i.e., IHC-IoT networks. To achieve this, the HOPCTP prototype promotes data preservation and communication in terms of authenticity, congestion, throughput, communication cost, and packet loss ratio. The result statistics of the proposed scheme demonstrate remarkable improvement over the existing schemes for aforementioned comparative metrics.
Keywords: Authentication of patient wearable device; Computational modelling; Data preservations; High optimal path channel triggering protocol protocol; Medical services; Optimal paths; Security; Security in industrial healthcare internet of thing; Transmission channels; Wearable devices; Authentication of patient wearable device; data preservation; high optimal path channel triggering protocol (HOPCTP); security in Industrial Healthcare Internet of Things (IHC-IoT); transmission channels